Gender Bias in The Rural Community as Reflected in Minfong Hoâs Sing to The Dawn - Wahyaka, Hermanus (LLT Journal: A Journal on Language and Language Teaching, 2012)
This study aims at identifying the evidences of gender-biased behaviour and actions and at finding the possible reasons why those gender-biased behaviour and actions happen within the life of the rural community as depicted in the novel. The problems, therefore, are formulated as follows: 1). What are the evidences of gender-biased behaviour and actions experienced by the major female characters of HoâsSing to the Dawn?and 2). Why do the gender-biased behaviour and actionsÂ occur within the life of the rural communityas in HoâsSing to the Dawn? This study is a library research. The primary source is the novel itself, Sing to the Dawn. The secondary sources are obtained from several relevant books related to literary theories such as the critical approach, the theory of gender, the theory of society, and the review of Thai society. In order to relate the gender bias and a certain community, the socio-cultural approach is used to examine the novel. This study found that gender biased behaviour and actions committed by the male characters towards the major female characters manifest in several manners; they are subordination of women, mental violence, violent intention, physical violence, sex role stereotyping, and marginalization. The possible reasons enabling the manifestation of gender biased behaviour and actions committed by the male characters towards the major female characters are cultural construction on women subordination, cultural construction on sex roles stereotyping as the result of patriarchal system, religious misinterpretation, and poverty.Â DOI: https://doi.org/10.24071/llt.2012.150205